Nonlinear behavior of the surface waves between two magnetic fluid layers - Zakaria, Kadry; Sirwah, Magdy A (Physica scripta, 2012)
In this paper, we provide an extensive stability analysis of the surface waves between two immiscible infinite layers of magnetic liquids. This subject seems to have a long history with relevance to fluid mechanics as well as technological and industrial applications. The effects of gravitation and a uniform oblique magnetic field are taken into account. The analytical solutions of the nonlinear problem are achieved in the framework of the perturbation analysis methods, in order to treat finite amplitude waves and then determine the stability criteria of the considered problem. The various stability criteria of the traveling waves are investigated. Also, the solitary-wave solutions at the liquid-liquid interface are discussed. In the end, the effort comes across as a number of snapshots of neutral stability curves in the parameter space. The influence of different parameters governing the flow on the stability behavior of the system is discussed in detail.